A spraying material admixture and its preparation method and application
By combining guar gum, copolymers, and modifiers, the compressive strength and adhesion of the sprayed mortar material are improved, solving the problem of easy delamination between the sprayed mortar material and the substrate. This results in a sprayed mortar material with high adhesion and high stability, improving the durability of buildings and construction efficiency.
Patent Information
- Application Number
- CN202510504531.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2025-10-28
- Estimated Expiration
- 2045-04-22
AI Technical Summary
Existing shotcrete materials suffer from poor adhesion, unstable construction quality, low construction efficiency, and insufficient building stability and durability during construction. In particular, the easy delamination between the shotcrete material and the substrate leads to cracking and poor durability of the building.
By combining guar gum, copolymers, and modifiers, a copolymer is generated through the reaction of pentaerythritol triacrylate and pyromellitic acid, which increases the compressive strength and density of the sprayed material. A modifier is generated through the reaction of resveratrol oxide, sodium gluconate, and isocyanate, which improves the adhesion and compressive strength, and enhances the adhesion between the sprayed material and the substrate.
It improves the adhesion between the sprayed grout and the substrate, enhances the compressive strength and density of the sprayed grout, reduces the shrinkage rate, improves the stability and durability of the building, and solves the problems of easy delamination and cracking during construction.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of concrete admixtures, specifically relating to a shotcrete material admixture, its preparation method, and its application. Background Technology
[0002] Shotcrete is a type of coating that can be used on building surfaces, widely applied for the decoration and protection of exterior walls, interior walls, roofs, and floors. However, with the increasing complexity of engineering construction environments, the limitations of traditional shotcrete in terms of high-efficiency and high-quality construction have become increasingly apparent. These limitations include unstable construction quality, low construction efficiency, and insufficient stability and durability of the building after construction. One of the key reasons for these problems is the insufficient adhesion between the shotcrete and the construction interface, leading to delamination between the shotcrete and the substrate, thus weakening the stability and durability of the building. To improve upon the shortcomings of traditional shotcrete and meet the needs of modern engineering construction, researchers in this field have developed various types of shotcrete admixtures.
[0003] Patent CN115784664B discloses an anti-permeability accelerator and its preparation method. The raw materials for preparing the anti-permeability accelerator include the following components by weight percentage: 60%-70% accelerator, 6%-10% solubilizer, 2%-3% early strength agent, 2%-3% rebound inhibitor, 1%-2% viscosity reducer, 1%-1.5% naphthalene-based water-reducing agent, 0.5%-1% suspending agent, 0.01%-0.02% defoamer, and the remainder is water; the rebound inhibitor includes at least one of styrene-butadiene latex and hydrophobic chemical plugging agent. This anti-permeability accelerator improves the anti-permeability performance of shotcrete by synergistically combining various additives, thereby enhancing the stability of shotcrete. However, the use of naphthalene-based water-reducing agent in this anti-permeability accelerator not only has relatively poor adaptability to cement types, but may also generate certain environmental pollution during production and use, and its raw material cost is relatively high.
[0004] Patent CN110105012A discloses a high-performance admixture for shotcrete. This admixture comprises two main components: a cohesive component and an early-strength component, with a mass ratio of 60-70:30-40. The cohesive component is a mixture of modified latex powder and ultrafine mineral admixtures, with a mass ratio of 20-30:70-80. The early-strength component is highly active tricalcium aluminate. This invention effectively improves the cohesiveness and early strength of shotcrete, enhances its density, and improves its overall performance through the synergistic effect of the cohesive and early-strength components. However, the addition of a large amount of ultrafine mineral powder can lead to significant concrete shrinkage and increased susceptibility to cracking.
[0005] Therefore, there is an urgent need in the market for a shotcrete material admixture that is adaptable and does not shrink easily after construction. Summary of the Invention
[0006] To overcome the shortcomings of the prior art, the present invention provides a spraying material admixture and its preparation method. The admixture prepared by the present invention can effectively reduce the shrinkage of concrete, increase compressive strength, and has high adhesion to the substrate.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] The first aspect of the present invention provides a spraying material additive, which, by weight, comprises the following raw materials: 0.8-1 parts of guar gum, 25-30 parts of copolymer, 2-5 parts of modifier, 0.2-0.4 parts of initiator, and 90-100 parts of solvent.
[0009] In some embodiments, the method for preparing the copolymer includes the following steps:
[0010] (1) Add pentaerythritol triacrylate, pyromellitic acid, and hydroquinone to dichloromethane, heat to 70-80℃ and add concentrated sulfuric acid, then continue the reaction for 7-8 hours, wash and dry to obtain the compound;
[0011] (2) Add the compound obtained in step (1), pentaerythritol, allyl glycidyl ether and catalyst into a reaction vessel, heat to 160-200℃, and stir at -0.1Kpa to 1Kpa for 3-4h to obtain the copolymer.
[0012] This invention selects pentaerythritol triacrylate containing double bonds and hydroxyl groups and pyromellitic acid containing multiple carboxyl groups, and then reacts the two to obtain a compound containing multiple double bonds and carboxyl groups. This compound is then reacted with pentaerythritol and allyl glycidyl ether to obtain a copolymer, which is used to prepare an admixture for sprayed grout materials. This copolymer can improve the compressive strength of the sprayed grout material while reducing shrinkage and cracking. The reason for this is likely that the multiple double bonds in the copolymer react with guar gum to form a cross-linked structure. During mixing with the sprayed grout material, the grout material can be "interspersed" within the admixture, increasing the density of the sprayed grout material, reducing shrinkage, and improving compressive strength. Furthermore, during cement hydration in the sprayed grout material, the ester groups in the copolymer partially hydrolyze, regenerating carboxylic acids, which improves the dispersibility of cement particles and reduces the slump of the sprayed grout material. In addition, the presence of numerous polar groups makes the bond between the substrate and the sprayed material tighter, further increasing the stability and durability of the building.
[0013] In some embodiments, the mass ratio of pentaerythritol triacrylate to pyromellitic acid is 1:(0.9-1.3).
[0014] In some embodiments, the mass ratio of the compound in step (2) to pentaerythritol is 1:(0.7-1).
[0015] In some embodiments, the mass ratio of the compound in step (2) to allyl glycidyl ether is 1:(0.05-0.15).
[0016] This invention allows one carboxyl group of pyromellitic acid to participate in the reaction by limiting the mass ratio of pentaerythritol triacrylate and pyromellitic acid, and enables the compound to react with pentaerythritol and allyl glycidyl ether by limiting the mass ratio of the compound to pentaerythritol and allyl glycidyl ether, thereby increasing the compressive strength of the sprayed material.
[0017] In some embodiments, the preparation method of the modifier includes the following steps: adding resveratrol oxide, sodium gluconate, isocyanate, trans-1,2,3-propenylic acid and butyltin dilaurate to acetone, reacting at 70-80°C for 1-2 hours, and drying to obtain the modifier.
[0018] Preferably, the isocyanate is isophorone diisocyanate.
[0019] This invention provides a modifier with a special structure obtained through the reaction of oxidized resveratrol, sodium gluconate, isocyanate, and trans-1,2,3-propenylic acid. This modifier improves the adhesion, density, and compressive strength of the sprayed grout material. The possible reason is that the modifier reacts with guar gum to further enhance the crosslinking degree of the admixture, making both more compact. This compensates for the reduced crosslinking degree and density that may result from the partial hydrolysis of ester groups in the copolymer. Furthermore, the amino groups on the modifier further enhance the interaction force with the substrate, improving adhesion. The addition of the modifier also further reduces the viscosity of the sprayed grout material, increases its fluidity, reduces water usage, facilitates construction, shortens setting time, reduces slump loss, and promotes cement hydration in the sprayed grout material, thereby increasing the strength and durability of the sprayed grout material.
[0020] In some embodiments, the mass ratio of oxidized resveratrol to isocyanate is (0.1-0.3):1.
[0021] In some embodiments, the sodium gluconate to isocyanate ratio is (0.7-1.2):1.
[0022] In some embodiments, the mass ratio of trans-1,2,3-propenylic acid to isocyanate is (1-1.5):1.
[0023] This invention increases the crosslinking degree of the modifier and guar gum by limiting the mass ratio of oxidized resveratrol to isocyanate, thereby improving compressive strength; it reduces the amount of water used by limiting the mass ratio of sodium gluconate to isocyanate, while avoiding excessive water use that could lead to a decrease in the stability of the sprayed material; and it further enhances the compressive strength and stability of the sprayed material by limiting the amount of trans-1,2,3-propenylic acid tricarboxylic acid to isocyanate, while also mitigating the problems of increased brittleness, cracking, and decreased durability of buildings caused by the oxidation of double bonds.
[0024] In some embodiments, the initiator is azobisisobutyrazoline hydrochloride.
[0025] The present invention preferably uses azobisisobutyrazoline hydrochloride as an initiator, which has good solubility in water. Compared with commonly used azonitrile initiators, it does not contain cyano groups, and its decomposition products are non-toxic, safe and environmentally friendly. In addition, it produces very little residue and agglomeration during the reaction process, which can significantly improve the quality and performance of the additive.
[0026] A second aspect of the present invention provides a method for preparing an admixture for sprayed mortar materials, comprising the following steps:
[0027] S1. Solution preparation: Add guar gum to half the weight of the solvent, heat to 40-60℃ and stir for 60-90 minutes to obtain guar gum solution;
[0028] Add the modifier and copolymer to the remaining solvent and stir for 30-50 minutes to obtain a mixture;
[0029] S2. Add the mixture obtained in step S1 to the guar gum solution, then add the initiator, react at 65-75℃ for 3-4 hours, dry, and pulverize to obtain the building spraying material admixture.
[0030] A third aspect of the present invention provides an application of an admixture in a shotcrete material, wherein the admixture accounts for 5-10 wt% of the shotcrete material.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. This invention provides an additive for shotcrete materials by using guar gum, copolymers, modifiers, and other auxiliaries. This additive enhances the adhesion between the shotcrete material and the building, while also increasing the compressive strength of the shotcrete material, increasing its density, reducing shrinkage, and improving the stability and durability of the building.
[0033] 2. This invention selects pentaerythritol triacrylate containing double bonds and hydroxyl groups and pyromellitic acid containing multiple carboxyl groups, and then reacts the two to obtain a compound containing multiple double bonds and carboxyl groups. Then, it reacts with pentaerythritol and allyl glycidyl ether to obtain a copolymer, which is used to prepare an admixture for building sprayed mortar materials. This solves the problems of easy shrinkage and cracking of conventional sprayed mortar materials, and at the same time improves the compressive strength of sprayed mortar materials.
[0034] 3. This invention obtains a modifier with a special structure through the reaction between oxidized resveratrol, sodium gluconate, isocyanate and trans-1,2,3-propenylic acid, which improves the adhesion and density of the sprayed grout material, solves the problems of troublesome construction and high slump loss of ordinary sprayed grout materials, and improves the compressive strength and durability of the sprayed grout material. Detailed Implementation
[0035] The present invention will be described below with reference to specific embodiments. It should be noted that the examples and comparative examples below are for illustrative purposes only and are not intended to limit the invention. Other combinations and various modifications within the scope of the invention can be made without departing from its spirit or scope.
[0036] To facilitate implementation of this invention by those skilled in the art, the following description is provided regarding some of the raw materials and manufacturers used in the embodiments and comparative examples:
[0037] The compounds and related reagents used in the following examples and comparative examples are all commercially available. The spraying material is shotcrete, which was purchased from Beijing Huashengkangda Engineering Technology Co., Ltd.
[0038] Preparation Example 1
[0039] The preparation method of copolymer-1 includes the following steps:
[0040] (1) 10g pentaerythritol triacrylate, 11g pyromellitic acid, and 0.01g hydroquinone were added to 200ml dichloromethane, heated to 75℃, and 5ml 95wt% concentrated sulfuric acid was added. The reaction was continued for 7.5h. The mixture was washed and dried to obtain the compound.
[0041] (2) Add 10g of the compound obtained in step (1), 9g of pentaerythritol, 1g of allyl glycidyl ether and 0.1g of tetrabutyl titanate into a reaction vessel, heat to 180℃, and stir at -0.1Kpa for 3.5h to obtain copolymer-1.
[0042] Preparation Example 2
[0043] The preparation method of copolymer-2 is the same as that of preparation example 1, except that the amount of pyromellitic acid added is 7g.
[0044] Preparation Example 3
[0045] The preparation method of copolymer-3 is the same as that of preparation example 1, except that the amount of pentaerythritol added is 12g.
[0046] Preparation Example 4
[0047] The preparation method of copolymer-4 is the same as that of preparation example 1, except that allyl glycidyl ether is not added.
[0048] Preparation Example 5
[0049] The preparation method of modifier-1 includes the following steps: 2g of resveratrol oxide, 10g of sodium gluconate, 10g of isophorone diisocyanate, 13g of trans-1,2,3-propenylic acid and 0.2g of butyltin dilaurate are added to 100ml of acetone, reacted at 75℃ for 1.5h, and dried to obtain modifier-1.
[0050] Preparation Example 6
[0051] The preparation method of modifier-2 is the same as that of preparation example 5, except that the amount of oxidized resveratrol added is 5g.
[0052] Preparation Example 7
[0053] The preparation method of modifier-3 is the same as that of preparation example 5, except that the amount of sodium gluconate added is 15g.
[0054] Preparation Example 8
[0055] The preparation method of modifier-4 is the same as that of preparation example 5, except that trans-1,2,3-propenylic acid is not added.
[0056] Example 1
[0057] An additive for spraying materials, by weight, comprises the following raw materials: 0.9 parts guar gum, 28 parts copolymer-1, 4 parts modifier-1, 0.3 parts azobisisobutyrazoline hydrochloride, and 95 parts water.
[0058] The preparation method of the spraying material admixture in this embodiment includes the following steps:
[0059] S1. Preparation of solution: Add guar gum to half the weight of water, heat to 50°C and stir for 75 minutes to obtain guar gum solution;
[0060] Modifier-1 and copolymer-1 were added to the remaining water and stirred for 40 minutes to obtain a mixture.
[0061] S2. Add the mixture obtained in step S1 to the guar gum solution, then add azobisisobutyrazoline hydrochloride, react at 70℃ for 3.5h, dry, and pulverize to obtain the spraying material additive.
[0062] Example 2
[0063] An additive for spraying materials, by weight, comprises the following raw materials: 0.8 parts guar gum, 25 parts copolymer-1, 2 parts modifier-1, 0.2 parts azobisisobutyrazoline hydrochloride, and 90 parts water.
[0064] The preparation method of the spraying material admixture in this embodiment includes the following steps:
[0065] S1. Preparation of solution: Add guar gum to half the weight of water, heat to 40°C and stir for 90 minutes to obtain guar gum solution;
[0066] Add modifier-1 and copolymer-1 to the remaining water and stir for 30 minutes to obtain a mixture;
[0067] S2. Add the mixture obtained in step S1 to the guar gum solution, then add azobisisobutyrazoline hydrochloride, react at 65°C for 4 hours, dry, and pulverize to obtain the spraying material additive.
[0068] Example 3
[0069] An additive for spraying materials, by weight, comprises the following raw materials: 1 part guar gum, 130 parts copolymer, 1.5 parts modifier, 0.4 parts azobisisobutyrazoline hydrochloride, and 100 parts water.
[0070] The preparation method of the spraying material admixture in this embodiment includes the following steps:
[0071] S1. Preparation of solution: Add guar gum to half the weight of water, heat to 60°C and stir for 60 minutes to obtain guar gum solution;
[0072] Add modifier-1 and copolymer-1 to the remaining water and stir for 50 minutes to obtain a mixture;
[0073] S2. Add the mixture obtained in step S1 to the guar gum solution, then add azobisisobutyrazoline hydrochloride, react at 75°C for 3 hours, dry, and pulverize to obtain the spraying material additive.
[0074] Example 4
[0075] An additive for spraying material and its preparation method are disclosed. The specific implementation method is the same as that in Example 1, except that copolymer-1 is replaced with copolymer-2 in equal amounts.
[0076] Example 5
[0077] An additive for spraying material and its preparation method are disclosed. The specific implementation method is the same as that in Example 1, except that copolymer-1 is replaced with copolymer-3 in equal amounts.
[0078] Example 6
[0079] An additive for spraying material and its preparation method are disclosed. The specific implementation method is the same as that in Example 1, except that copolymer-1 is replaced with copolymer-4 in equal amounts.
[0080] Example 7
[0081] An admixture for sprayed mortar and its preparation method are described. The specific implementation method is the same as in Example 1, except that modifier-1 is replaced with modifier-2 in equal amounts.
[0082] Example 8
[0083] An admixture for spraying material and its preparation method are described. The specific implementation method is the same as in Example 1, except that modifier-1 is replaced with modifier-3 in equal amounts.
[0084] Example 9
[0085] An admixture for spraying material and its preparation method are described. The specific implementation method is the same as in Example 1, except that modifier-1 is replaced with modifier-4 in equal amounts.
[0086] Comparative Example 1
[0087] An additive for spraying material and its preparation method are described. The specific implementation method is the same as in Example 1, except that no modifier is added.
[0088] Performance testing
[0089] 1. Compressive strength
[0090] The admixtures obtained in each embodiment and comparative example were added to the sprayed grout material at 8 wt%, then placed into a cube mold with a side length of 100 mm and vibrated to compact it using an electric vibration table. After 24 hours, the mold was removed, and the material was cured for 28 days at a temperature of 25°C and a relative humidity of 95% to obtain test blocks. The compressive strength was tested in accordance with GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete".
[0091] 2. Shrinkage resistance
[0092] The admixtures obtained from each embodiment and comparative example were added to the shotcrete material at 8 wt%. The shrinkage rate on day 1 and day 180 was tested according to the method described in 8.1 of GB / T5008-2009 Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete. The ratio of the shrinkage rate on day 180 to that on day 1 for each embodiment and comparative example was calculated and recorded as the relative shrinkage rate.
[0093] 3. Adhesion
[0094] Using smooth red bricks as the substrate, the additives obtained in each embodiment and comparative example were added to the spraying material at 8 wt% and uniformly sprayed onto the surface of the red bricks to form a covering layer with a thickness of about 20 mm × 20 mm × 5 mm as a sample. The sample was cured for 28 days at a temperature of 25°C and a relative humidity of 95%. The maximum tensile strength was tested using a portable pull-out tester. The pull-out tester was used to uniformly apply tensile force until the sample separated from the substrate surface, and the value at this time was recorded as the maximum tensile strength value to evaluate the adhesion performance of the material.
[0095] The experimental results are shown in Table 1.
[0096] Table 1
[0097] Group Compressive strength / MPa Relative shrinkage rate / % Maximum tensile strength / N Example 1 45.3 51.2 43.23 Example 2 42.1 52.3 41.45 Example 3 44.1 51.5 42.89 Example 4 40.1 55.3 42.46 Example 5 41.4 56.5 43.64 Example 6 37.8 52.1 38.11 Example 7 35.5 52.6 41.89 Example 8 34.3 51.7 42.97 Example 9 32.8 52.9 37.84 Comparative Example 1 30.1 58.3 35.18
[0098] A comparison of the experimental data from Examples 1-3 in Table 1 shows that the additive imparts good compressive strength, adhesion, and shrinkage resistance to the sprayed material. A comparison of Examples 4 and 5 with Example 1 shows that changes in the ratio of pentaerythritol triacrylate to pyromellitic acid and the ratio of the compound to pentaerythritol may alter the degree of crosslinking of the copolymer, leading to a decrease in both the compressive strength and shrinkage resistance of the sprayed material. A comparison of Example 6 with Example 1 shows that the absence of allyl glycidyl ether may reduce the adhesiveness of the additive, resulting in a decrease in both the compressive strength and adhesion of the sprayed material. A comparison of Example 7 with Example 1 shows that… It is known that changing the ratio of oxidized resveratrol to isocyanate may increase the brittleness of the admixture and decrease its compressive strength. A comparison of Example 8 and Example 1 shows that changing the ratio of sodium gluconate to isocyanate may delay the hydration reaction of cement in concrete, resulting in a decrease in the compressive strength of the sprayed material. A comparison of Example 9 and Example 1 shows that not adding trans-1,2,3-propenylic acid may affect its reaction with the copolymer, resulting in a decrease in the adhesion of the admixture and a certain degree of decrease in compressive strength. A comparison of Comparative Example 1 and Example 1 shows that without the addition of a modifier, all properties of the sprayed material are reduced.
[0099] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A spraying material admixture, characterized in that, By weight, it contains the following raw materials: 0.8-1 parts guar gum, 25-30 parts copolymer, 2-5 parts modifier, 0.2-0.4 parts initiator, and 90-100 parts solvent; The method for preparing the copolymer includes the following steps: (1) Add pentaerythritol triacrylate, pyromellitic acid, and hydroquinone to dichloromethane, heat to 70-80℃, add concentrated sulfuric acid, and continue the reaction for 7-8 hours. Wash and dry to obtain the compound. (2) Add the compound obtained in step (1), pentaerythritol, allyl glycidyl ether and catalyst into a reaction vessel, heat to 160-200℃, and stir at -0.1KPa~1KPa for 3-4h to obtain the copolymer; The mass ratio of pentaerythritol triacrylate to pyromellitic acid is 1:(0.9-1.3). The mass ratio of the compound to pentaerythritol in step (2) is 1:(0.7-1); The preparation method of the modifier includes the following steps: adding oxidized resveratrol, sodium gluconate, isocyanate, trans-1,2,3-propenylic acid and butyltin dilaurate into acetone, reacting at 70-80℃ for 1-2 hours, and drying to obtain the modifier; The mass ratio of oxidized resveratrol to isocyanate is (0.1-0.3):1; The mass ratio of sodium gluconate to isocyanate is (0.7-1.2):
1.
2. The admixture for shotcrete materials according to claim 1, characterized in that, The initiator is azobisisobutyrazoline hydrochloride.
3. A method for preparing the admixture for shotcrete materials according to any one of claims 1-2, characterized in that, Includes the following steps: S1. Solution preparation: Add guar gum to half the weight of the solvent, heat to 40-60℃ and stir for 60-90 minutes to obtain guar gum solution; Add the modifier and copolymer to the remaining solvent and stir for 30-50 minutes to obtain a mixture; S2. Add the mixture obtained in step S1 to the guar gum solution, then add the initiator, react at 65-75℃ for 3-4 hours, dry, and pulverize to obtain the spraying material additive.
4. The application of a spraying material admixture according to any one of claims 1-2 or a spraying material admixture obtained by the preparation method according to claim 3, characterized in that, The admixture accounts for 5-10 wt% of the shotcrete material.
Citation Information
Patent Citations
Admixture special for high performance shotcrete
CN110105012A
Viscous-state hydrogenated nitrile rubber as well as preparation method and application thereof
CN118909566A
Active energy ray-curable antistatic coating composition
JP2010077438A